2008
DOI: 10.1523/jneurosci.2254-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Plasticity Induced by Short-Term Unimodal and Multimodal Musical Training

Abstract: Learning to play a musical instrument requires complex multimodal skills involving simultaneous perception of several sensory modalities: auditory, visual, somatosensory, as well as the motor system. Therefore, musical training provides a good and adequate neuroscientific model to study multimodal brain plasticity effects in humans. Here, we investigated the impact of short-term unimodal and multimodal musical training on brain plasticity. Two groups of nonmusicians were musically trained over the course of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
200
4
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(225 citation statements)
references
References 44 publications
16
200
4
4
Order By: Relevance
“…However, future studies that formally compare the effect of pure audiovisual vs. audiovisual-motor training schemes on audiovisual synchrony perception are needed to further dissociate the contributions of sensory-motor from pure audiovisual (i.e., sensory) learning effects. In the unisensory domains, the role of audio-motor experience has recently been highlighted in a magnetoencephalography (MEG) study showing a larger mismatch negativity for deviant musical structures after audio-motor (i.e., piano practicing) than pure auditory learning (39). Conversely, studies comparing motor skills that are and are not associated with sounds (e.g., pianists vs. athletes) are needed to confirm that motor skills per se do not afford higher sensitivity to the temporal misalignment of auditory and visual signals.…”
Section: Resultsmentioning
confidence: 99%
“…However, future studies that formally compare the effect of pure audiovisual vs. audiovisual-motor training schemes on audiovisual synchrony perception are needed to further dissociate the contributions of sensory-motor from pure audiovisual (i.e., sensory) learning effects. In the unisensory domains, the role of audio-motor experience has recently been highlighted in a magnetoencephalography (MEG) study showing a larger mismatch negativity for deviant musical structures after audio-motor (i.e., piano practicing) than pure auditory learning (39). Conversely, studies comparing motor skills that are and are not associated with sounds (e.g., pianists vs. athletes) are needed to confirm that motor skills per se do not afford higher sensitivity to the temporal misalignment of auditory and visual signals.…”
Section: Resultsmentioning
confidence: 99%
“…Although preexisting differences can influence musical activity and abilities, it is also clear that auditory abilities and their underlying neural substrates are highly malleable due to experience (e.g., Alain et al, 2007;Lappe et al, 2008). Thus, it is likely that although differences in personality or preexisting perceptual abilities might lead some individuals to choose to learn a musical instrument or play music video games, the actual experience of practicing these activities is what leads to differences in music aptitude.…”
Section: Discussionmentioning
confidence: 99%
“…The past two decades have nevertheless witnessed an abundance of reports suggesting that "musicians" outperform "nonmusicians" on measures of sensory, cognitive, and motor functions (Hannon & Trainor, 2007;Strait & Kraus, 2014). Studies with tightly controlled learning situations have demonstrated that remarkable behavioral and neural changes can occur as a result of auditory learning (e.g., Alain, Snyder, He, & Reinke, 2007;Lappe, Herholz, Trainor, & Pantev, 2008), or even passive exposure to musical stimuli (e.g., Hannon & Trehub, 2005). However, other evidence suggests that personality differences predict who undertakes music training and who does not (e.g., Corrigall, Schellenberg, & Misura, 2013).…”
mentioning
confidence: 99%
“…Indeed, assignment to musical training has been found to yield structural changes in auditory and motor cortices that correlate with performance on melody discrimination and finger tapping tasks, respectively ( Although the above results suggest some transfer attributable to musical training (see also Lappe et al, 2008;Besson et al, 2011), one remaining question is whether the occurrence of transfer is selective to specific points in development. Can musical training-related cognitive differences persist beyond childhood?…”
Section: Expertise and Generalizationmentioning
confidence: 97%